2018
DOI: 10.1007/s11103-018-0725-x
|View full text |Cite
|
Sign up to set email alerts
|

A genome-wide analysis of the flax (Linum usitatissimum L.) dirigent protein family: from gene identification and evolution to differential regulation

Abstract: Identification of DIR encoding genes in flax genome. Analysis of phylogeny, gene/protein structures and evolution. Identification of new conserved motifs linked to biochemical functions. Investigation of spatio-temporal gene expression and response to stress. Dirigent proteins (DIRs) were discovered during 8-8' lignan biosynthesis studies, through identification of stereoselective coupling to afford either (+)- or (-)-pinoresinols from E-coniferyl alcohol. DIRs are also involved or potentially involved in terp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
103
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(108 citation statements)
references
References 115 publications
5
103
0
Order By: Relevance
“…Thus, in our study, the high expression of FPGS in the alligator weed leaves could improve the lignin content in the cell wall in order to protect cells under LK stress. Corbin et al reported that some direct proteins (DIRs) can be involved in secondary cell wall biosynthesis and plant defense in flax [24]. In our study, one DIR was up-regulated, underlying the universal roles DIRs play in plant abiotic stress response.…”
Section: Go Term and Kegg Pathway Analyses Of Daps Under Lk Stresssupporting
confidence: 52%
“…Thus, in our study, the high expression of FPGS in the alligator weed leaves could improve the lignin content in the cell wall in order to protect cells under LK stress. Corbin et al reported that some direct proteins (DIRs) can be involved in secondary cell wall biosynthesis and plant defense in flax [24]. In our study, one DIR was up-regulated, underlying the universal roles DIRs play in plant abiotic stress response.…”
Section: Go Term and Kegg Pathway Analyses Of Daps Under Lk Stresssupporting
confidence: 52%
“…For MpMYB14, this includes the three DIR genes discussed earlier as well as other DIR genes that have been shown to be direct targets (Kubo et al, 2018). Co-expression analysis in flax found that MYB TFs were up-regulated along with DIR genes during secondary wall biosynthesis (Corbin et al, 2018), suggesting that MYB proteins could control DIR expression in both angiosperms and bryophytes.…”
Section: Evolution Of the Transcriptional Regulation Of The Phenylpromentioning
confidence: 94%
“…The role of DIRs in determining stereospecificity has been best described in the formation of lignans, a class of 8-8' linked C 6 C 3 phenylpropanoid dimers involved in pathogen resistance, for example in the production of (+)-or (−)-pinoresinol compounds in flax (Linum usitatissimum) and pea (Pisum sativum) Corbin et al, 2018). The X-ray crystal structure of PsDRR206 involved in (+)-pinoresinol formation suggested that the active protein had a trimeric structure .…”
Section: Liverworts May Have Expanded Functional Roles In Specializedmentioning
confidence: 99%
See 1 more Smart Citation
“…The early biosynthetic steps of lignans' formation have been well characterized [17]. First, a dirigent protein (DIR) (LuDIR1, LuDIR5 or LuDIR6 for in flax) directs the stereoselective radical-radical coupling of two E-coniferyl alcohol radical units into pinoresinol [18][19][20]. Pinoresinol is then reduced into secoisolariciresinol by a stereoselective pinoresinol-lariciresinol reductase (PLR) enzyme, via lariciresinol formation.…”
Section: Introductionmentioning
confidence: 99%